Meta-análise e estudo de associação na busca de biomarcadores de diagnóstico nos genes CD2AP e MS4A4E para a doença de Alzheimer - Almeida, Jucimara Ferreira Figueiredo (2018)
Alzheimer's disease (AD) is one of the most common types of dementia. It has pathological changes, such as amyloid plaques and neurofibrillary tangles. In 98% of the cases, AD is sporadic or late-onset AD (LOAD) and presents a multifactorial characteristic. Variants rs670139 in MS4A4E gene and rs9349407 in CD2AP gene were considered associated with the risk in LOAD in studies with Genome wide association studies. The clinical diagnosis of AD is difficult and is only possible when the disease is already in advanced stages, so the studies are seeking to find biomarkers to help diagnose the disease in the early stages. Thus, in recent years, several case-control studies have been published investigating the association of rs670139 MS4A4E gene and rs9349407 CD2AP gene with LOAD in other populations. Thus, this study aimed to investigate the association between rs670139 MS4A4E and rs9349407 CD2AP with LOAD in a sample of individuals from Grande Vitória, ES and conduct an updated meta-analysis study on the association of these variants with the disease. The study performed was an association study with 221 individuals not consanguineous, including 139 individuals without Dementia matched by sex and age and 82 patients with diagnosis of probable LOAD. It was performed Polymerase Chain Reaction – Restriction Fragment Length Polymorphism for genotyping. As statistical analysis, it was performed Chi-square test, Odds ratio (Confidential interval of 95%), Mann-Whitney and Logistic regression at SPSS software. It was considered p significance with value < 0.05. It was also calculated the Hardy-Weinberg Equilibrium for each group. The genotype results were validated by sequencing in 5% of the samples. In the meta-analysis, the allelic comparison by additive genetic model was performed by R Program. The results obtained in this study suggest that the A allele of rs670139 MS4A4E is associated with risk in LOAD in meta-analysis. This result supports a role of risk of rs670139, since this SNP in functional studies has been correlated with increased amyloid plaques. However, there is no association of rs670139 MS4A4E and rs9349407 CD2AP polymorphisms with LOAD in the population of Grande Vitória, ES and the meta-analysis there is no association of rs9349407 CD2AP polymorphisms with LOAD. The results of this work are important to help validate the role of genetic variants on the risk for LOAD.